AN ETHNOGRAPHIC STUDY OF ENGLISH LEARNING AT SMK NEGERI I GORONTALO - Miolo, Sartin T.; Rasyid, Yumna (University of Kuningan, 2017)
This study aims to find out and understand more deeply and comprehensivelyabout English learning conducted at SMK Negeri I Gorontalo. Sources of data in this study are English teachers and students of SMK Negeri I Gorontalo grade XI second semester of 2015/2016 school academic year. Data were collected through observation, interview and data recording and documentation. The approach used in this research was thequalitative approach through ethnography method. The results showed that the methods and approaches used by teachers in learning arean integrated approach of genre-based scientific using whole language method. Sufficient learning media to support the learning and the role of teachers and learners who support each other in learning is constructive so that the learning process becomes interesting and fun. The conclusion that the use of English language, achievement and competing for culture is done to help learners develop English proficiency.Keywords: Learning, English, Ethnography